Performance, Body Composition, and Behavior of Lambs Consuming Different Extruded Roughage to Concentrate Ratios - M. T. S. Siqueira; K. A. Oliveira; P. H. C. Ribeiro; L. C. Araújo; M. R. Oliveira; L. E. G. Vilaça; L. O. Faria; G. L. Macedo Júnior (Tropical Animal Science Journal, 2026)
High levels of roughage in the diet reduce energy density and limit voluntary intake due to ruminal physical constraints. In this context, extrusion processing can improve digestibility and enable greater fiber inclusion in the diet, thereby improving animal performance. The objective of this study was to evaluate the productive performance, body composition, and ingestive behavior of lambs that were fed different proportions of extruded roughage to concentrate (R:C). Twenty lambs, weighing 25.0 ± 2.8 kg and aged 120 ± 8 d, were distributed in a completely randomized design and fed one of four proportions of roughage to concentrate: 30:70; 40:60; 50:50; or 60:40. Lambs were housed in collective pens throughout the experimental period. Body weight (BW) and body condition score (BCS), body conformation (in vivo biometric measurements), average daily gain (ADG, g/d), and in vivo carcass characteristics were not influenced by the treatments (p>0.05). An increase in roughage levels linearly increased total chewing time (TCT) (p<0.05). In contrast, idle time (IT) decreased linearly (p<0.05). There was a quadratic and positive linear effect of evaluation day (p<0.05) for BW, BCS, in vivo biometric measurements, ADG during the periods between 15–30 d (p=0.03) and 75–90 d (p<0.05), and in vivo carcass characteristics (p<0.05). There was an interaction between R:C ratio and the day of assessment for loin eye area, with day 84 superior to day 0 (p<0.05). The inclusion of higher levels of roughage in fully extruded diets increases TCT and decreases IT without affecting productive performance or body composition in sheep.